Potensi Dan Sebaran Diameter Batang Terhadap Dugaan Sekuestrasi Karbon Pada Tegakan Dipterocarpaceae Di Taman Wisata Alam Sorong - Maruapey, Azis; Nanlohy, Lona H.; Saeni, Fajrianto; Ohorella, Syarif (Median : Jurnal Ilmu Ilmu Eksakta, 2024)
This research was carried out in the Sorong Nature Tourism Park (TWA) Forest area from August 2023. This research aims to determine potential, biomass per diameter, biomass per unit area; and the amount of carbon stored in stands of Dipterocarpaceae species in the Sorong TWA forest. The potential stands of dipterocarpaceae species found in the Sorong TWA forest are 398 trees or an average of 39.8 trees/ha. The types of dipterocarpaceae stands found were Resak (Vatica papuana), Mersawa (Anisoptera spp.), and Merawan (Hopea sangol). The distribution of dipterocarpaceae stands is quite even, with the Vatica species being very dominant, namely 156 trees or 15.6 trees/ha, Mersawa with 132 trees or 13.2 trees/ha, and Hopea with 110 trees or 11.0 trees/ha. The total standing biomass of dipterocarpaceae species was 38.82 tonnes/ha, with details for the Vatica species contributing the most biomass, namely 16.58 tonnes/ha, Mersawa 12.49 tonnes/ha and Hopea 9.75 tonnes/ha. Meanwhile, the total biomass per area is 3.88 tons per hectare. The greatest amount of biomass is stored in stands of trees with a diameter > 30 cm compared to those with a diameter < 30 cm. The stored carbon reserve content of dipterocarpaceae stands is 1.78 tonnes/ha, so assuming the Sorong TWA forest has an area of ​​945.90 ha, it is estimated that the amount of carbon stored in dipterocarpaceae stands is 1683.70 tonnes.